Persistent pulmonary hypertension late after neonatal aortic valvotomy: a consequence of an expanded surgical cohort. Issue 8 (14th July 2004) - Burch, M; Kaufman, L; Archer, N; Sullivan, I
Abstract : Background: Survival of neonates with critical aortic stenosis has improved over the past decade. Models based on morphological characteristics have been designed to help determine whether early survival is more likely after biventricular repair (surgical or balloon aortic valvotomy) or after a single ventricle staged palliative surgical strategy. However, late follow up data are lacking. Objective: To report follow up data on survivors of neonatal aortic valvotomy who had persistent pulmonary hypertension caused by restriction to left ventricular filling. Results: Of four medium term survivors of neonatal valvotomy for critical aortic stenosis who had persistent pulmonary hypertension, one died aged 4 years and the other three have severe limitation of effort tolerance. Conclusions: This previously unreported late complication of "successful" biventricular repair for neonatal critical aortic stenosis is an important consideration in determining the initial management.